Effects on hematological parameters, antioxidant and immune responses, AChE, and stress indicators of olive flounders, Paralichthys olivaceus, raised in bio-floc and seawater challenged by Edwardsiella tarda. Issue 97 (February 2020) - Kim, Jun-Hwan; Sohn, Saebom; Kim, Su Kyoung; Hur, Young Baek
Abstract: Studies on the resistance of fish raised in bio-floc systems against bacterial infection are limited. We aimed to evaluate the changes in hematological parameters, antioxidant and immune responses, stress indicators, and acetylcholinesterase (AChE) in olive flounder, Paralichthys olivaceus, raised in bio-floc and seawater for 10 months and, then, infected with Edwardsiella tarda at concentrations of 0 (control), 6.61 × 10 4, 6.61 × 10 5, 6.61 × 10 6, and 6.61 × 10 7  CFU/g fish for 7 days. The lethal concentration 50% was 4.32 × 10 7 in bio-floc and 3.11 × 10 6 in seawater. Hematological parameters were significantly decreased by E. tarda challenge, and plasma components were significantly changed. The superoxide dismutase, catalase, and glutathione-S-transferase activities, as antioxidant responses, were significantly increased after infection, whereas the reduced glutathione level was significantly decreased. The lysozyme activity was significantly increased and the AChE level was significantly decreased after infection. Cortisol and HSP 70, as stress indicators, were also significantly increased. The results indicate that E. tarda infection affected various physiological factors in P. olivaceus . Additionally, P. olivaceus raised in seawater were more susceptible to E. tarda infection than those raised in bio-floc. Graphical abstract: Image 1 Highlights: The 7 day LC50 was 4.32 × 10 7  CFU/g in bio-floc and 3.11 × 10 6  CFU/g in seawater. Hematological parameters, antioxidant and immune responses were significantly changed. The AChE and stress indicators were significantly affected. The susceptibility to E. tarda were more prominent in the flounders raised in seawater.